2016
DOI: 10.14202/vetworld.2016.1229-1232
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory animal models for esophageal cancer

Abstract: The incidence of esophageal cancer is rapidly increasing especially in developing countries. The major risk factors include unhealthy lifestyle practices such as alcohol consumption, smoking, and chewing tobacco to name a few. Diagnosis at an advanced stage and poor prognosis make esophageal cancer one of the most lethal diseases. These factors have urged further research in understanding the pathophysiology of the disease. Animal models not only aid in understanding the molecular pathogenesis of esophageal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Previously reported metastatic mouse models have been mostly subcutaneous tumor models . Furthermore, there are a few studies, which have reported orthotopic metastatic mouse models of esophageal cancer, however, of our knowledge, other orthotopic metastatic mouse models of cocultured EC with CAFs have not been reported . We have established and reported this esophageal orthotopic xenograft model, in which tumor volume and metastatic activity were evaluated by luciferase emission .…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported metastatic mouse models have been mostly subcutaneous tumor models . Furthermore, there are a few studies, which have reported orthotopic metastatic mouse models of esophageal cancer, however, of our knowledge, other orthotopic metastatic mouse models of cocultured EC with CAFs have not been reported . We have established and reported this esophageal orthotopic xenograft model, in which tumor volume and metastatic activity were evaluated by luciferase emission .…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, IR treatment was performed with an 8 Gy dose at 2 Gy/min on the tumor position in dorsolateral flanks with other body areas of mice protected with a lead cover. On 28, 35, 42 days post-inoculation, the tumor sizes were measured with a caliper [10]. Tumor volume (mm 3 ) was calculated as L 9 l 2 9 0.5 (L is the longest diameter, and l is the shortest diameter) [11].…”
Section: Human Esc Xenograft Mouse Model and Target Ir Treatmentmentioning
confidence: 99%
“…14,15 ALA treatment has shown to be effective in many POI animal models, such as in cyclophosphamide-induced and 4-vinyl cyclohexene dioxide induced POI rats. 16,17 Although the activities of ALA in the prevention of POI have been discovered, in-depth studies of mechanisms are lacking. In addition, a comprehensive elucidation of ALA's biological pathways and biomarkers has not yet been completed.…”
Section: Introductionmentioning
confidence: 99%